Interaction between nitroheterocyclic compounds with beta-cyclodextrins: Phase solubility and HPLC studies - de Melo, Nathalie F. S. [UNESP]; Grillo, Renato [UNESP]; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Elsevier B.V., 2008)
Chagas disease is a serious health problem for Latin America. Nitrofurazone (NF) and Hidroxymethylnitrofurazone (NFOH) are active against Trypanosoma cruzi. The effect of beta-cyclodextrin (beta-CD) and dimethyl-beta-cyclodextrin (DM-beta-CD) complexation on the UV absorption and retention time of nitrofurazone (NF) and its hydroxymethylated analog (NFOH) were studied in solution. The retention behavior was analyzed on a reversed phase C(18) column and the mobile phase used was acetonitrile-water (20/80 v/v), in which cyclodextrins (beta-CD or DM-beta-CD) were incorporated as a mobile phase additive. The decrease in the retention times of NF (or NFOH) with increasing concentration of HP-beta-CD enables the cleternnination of the complex stability constants by HPLC. A phase-solubility Study was performed. according to the method reported by Higuchi and Connors, to evaluate the changes of NF/NFOH in the complexation state, and the diagrams obtained suggested that it forms complexes with a stoichiometry of 1 : 1. This is an important Study for the characterization of potential formulations to be used as therapeutic options for the treatment of Chagas disease. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: nitroheterocyclic compounds; hydroxymethylnitrofurazone; cyclodextrin; HPLC; solubility isotherm